(untitled) (SCIÉNDO INGENIUM, 2023)
The purpose of this paper is to implement a web system to improve the budget control of an architectural and engineering company, designing a web system using the SCRUM framework, to avoid the loss of information, duplicating amounts, increasing profits, and decreasing administrative time, favoring the budget effectiveness and efficiency of the service level. The research is applied with a quantitative approach, in addition, the design is pre-experimental, the sample is composed of 10 elements, using Student’s t-test and Wilcoxon’s test as statistical techniques. The implementation of the web system had an impact on the budgetary control of the company’s cost centers with favorable results in the two indicators, a positive increase in the percentage of budgetary effectiveness of 23% was obtained and in the percentage of service level efficiency an improvement of 54% was obtained. In conclusion, the web system was successful, reliable, secure, and user-friendly, allowing the company to have greater control and understanding of its finances and to improve its level of service satisfactorily.